Penggunaan Media Ajar Buku Cerita terhadap Kemampuan Membaca Siswa Kelas III SDK Tilang - Siti Saharia; Fitriah (PT PUSTAKA CENDEKIA GROUP, 2024)
This research is to examine the use of storybook teaching media on the reading ability of class III students at SDK Tilang. This research is qualitative and uses a descriptive approach. The use of storybooks on the reading ability of class III students at SDK Tilang is the object of research. The research instrument is the researcher himself who is equipped with a data recording sheet. In this research, it was found that the use of storybooks could improve students' reading abilities. The data used in this research was collected by means of documentation and data analysis techniques used in this research. Based on the results of this research, it can be concluded that the use of storybook teaching media has great potential in improving students' reading skills. Therefore, it is recommended that teachers use teaching media more often in the learning process to support the achievement of learning objectives.